Mengembangkan Sikap Rasa Ingin Tahu (Curiosity) Pada Pelajaran Fisika Menggunakan Model Pembelajaran Flipped Classroom - Joko Krismanto Harianja (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
Curiosity is one of the attitudes that needs to be developed in learning activities. This research proved hat students' curiosity can be developed by selecting appropriate learning models. The flipped classroom learning model is one of good models to develop curiosity. In this research the action research (CAR) class has been chosen as a research method to analyze the increase in curiosity and the value of learning outcomes in class 12 Physics learning activities. The treatment given is to provide opportunities for students to study independently outside the school schedule to study the material provided and find out all forms of information needed. Students have the opportunity to work together in class giving reports on their learning outcomes by making presentations in class. The instrument used for part of the data collection technique is in the form of observation sheets, questionnaire sheets and question sheets containing questions in accordance with the material being studied. The data analysis technique was carried out using descriptive and quantitative qualitative analysis. The results of the research show that students' curiosity and student learning outcomes can be improved by using these learning models. The obtained data analysis of the also shows that the implementation of the flipped classroom learning model provides very significant benefits.